Paths to Asian medical knowledge - Leslie,Charles(Editor) Young,Allan.(Editor) (Comparative studies of health systems and medical care, 1992)
"Like its classic predecessor, Asian Medical Systems, Paths to Asian Medical Knowledge is guided by two central ideas: that medical traditions are based on coherent forms of practice and belief about illnesses, and that these systems are embedded in the symbols and world views that characterize the historical differences between civilizations. These new essays by leading scholars from Europe and North America focus on issues in the humoral and bio-medical traditions of several Asian countries.